Arduino MKR Analysis Using the RTC Alarm Method - I Gusti Made Ngurah Desnanjaya; I Nyoman Saputra Wahyu Wijaya; Wayan Gede Suka Parwita; I Made Aditya Nugraha (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2022)
The researcher analyzed the Real-Time Clock (RTC) alarm readings on the Arduino MKR Zero, Arduino MKR Wan 1300, and Arduino MKR GSM 1400. The Arduino MKR board compared the data with the accuracy of reading the RTC values. To support this research, experimental quantitative research methods were used, and an independent sample t-test was used. The use of this method is very suitable because this method displays numbers as data and also conducts experiments directly on the Arduino MKR board. Comparative measurement of the three MKR using the RTC Alarm get the average time difference. This average indicates the IC capability and accuracy of MKR. From the experimental results, MKR GSM 1400 has the greatest. Arduino MKR GSM 1400 is the Arduino MKR that has the fastest data response among the other two Arduino MKRs. So, to create or develop a project related to real-time data transmission, it is recommended to use the Arduino MKR GSM 1400.